Sport’s Impact on the Francophoneness of the Alberta Francophone Games (AFG) - Dallaire, Christine (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2003)
AbstractThis article discusses the conflict between two discourses on “sport” and how their intersection with discourses on the “francophone” shaped the Alberta Francophone Games (AFG). A brief description of the two discourses is articulated in the context of the AFG. Whereas the “discourse of excellence” emphasizes both sporting competitiveness and the reproduction of established technical and organizational standards, the “discourse of participation” promotes recreational sport and the modification of structural and technical criteria. The author outlines the three principal debates generated by the interaction of sport and francophone discourses: competitive vs. recreational Games; smaller “francophone” Games vs. bigger French-speaking Games; and sport vs. francophoneness. The conclusion points to the effects of this muddled discursive space on organizers’ practices leading them to focus on the development of an expertise in sport performance and in sport management rather than developing a more sophisticated knowledge of the promotion of francophoneness.